History‐indicated cervical cerclage in management of twin pregnancy. (29th August 2019) - Rottenstreich, A.; Levin, G.; Kleinstern, G.; Zigron, R.; Rottenstreich, M.; Elchalal, U.; Yagel, S.
ABSTRACT: Objective: Cervical cerclage, when performed in twin gestation, has been reported to be associated with poor outcome. However, the role of first‐trimester history‐indicated cerclage among women with a twin pregnancy and a history of preterm birth has not been evaluated. The aim of this study was to assess pregnancy outcomes among women with a twin pregnancy who underwent first‐trimester history‐indicated cervical cerclage compared with outcomes in those managed expectantly. Methods: This was a retrospective matched case–control study. The study group comprised all women with a twin pregnancy who had undergone first‐trimester history‐indicated cerclage during the period 2006 to 2017 at Hadassah‐Hebrew University Medical Center. A control group of women with a twin pregnancy who were managed expectantly was established by matching age, history of spontaneous preterm birth (20–36 weeks' gestation) and year of delivery. Pregnancy and delivery characteristics and neonatal outcomes were compared between the two groups. Results: Data from 82 women with a twin gestation were analyzed, of whom 41 underwent first‐trimester history‐indicated cerclage and 41 were matched controls who were managed expectantly. Gestational age at delivery was higher in the cerclage group than in those managed expectantly (median 35 vs 30 weeks; P < 0.0001). Rates of spontaneous preterm birth before 24 weeks (2.4% vs 19.5%; odds ratio (OR), 0.10 (95% CI, 0.01–0.87); P = 0.03), before 28 weeks (12.2% vs 34.1%; OR, 0.27 (95% CI, 0.09–0.84); P = 0.03), before 32 weeks (22.0% vs 56.1%; OR, 0.22 (95% CI, 0.08–0.58); P = 0.003) and before 34 weeks (34.1% vs 82.9%; OR, 0.11 (95% CI, 0.04–0.30); P < 0.0001) were significantly lower in the cerclage group than in the control group. Median birth weight was higher in the cerclage group (2072 g vs 1750 g; P = 0.003), with lower rates of low birth weight (< 2500 g) (65.0% vs 89.4%; P = 0.001) and very low birth weight (< 1500 g) (21.3% vs 37.9%; P = 0.03) than in the group managed expectantly. Rates were also lower in the cerclage group for stillbirth, admission to the neonatal intensive care unit, respiratory distress syndrome, intraventricular hemorrhage, necrotizing enterocolitis, sepsis, neonatal mortality and composite adverse neonatal outcome. Conclusions: History‐indicated cerclage performed in the first trimester, as compared with expectant management, in women with a twin pregnancy had an overall positive effect on pregnancy and neonatal outcomes. These findings suggest the need for adequate randomized trials on cerclage placement in this subset of women. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.